Formal verification of a group membership protocol using model checking - Valério Rosset (2007)
The development of safety-critical embedded applications in domains such as automotive or avionics is an exceedingly challenging intellectual task. This task can, however, be significantly simplified through the use of middleware that offers specialized fault-tolerant services. This middleware must provide a high assurance level that it operates correctly. In this paper, we present a formal verification of a protocol for one such service, a Group Membership Service, using model checking. Through this verification we discovered that although the protocol specification is correct, a previously proposed implementation is not.